The Influence of Giving Vegetable Waste Leachate as Liquid Organic Fertilizer on the Growth of Mustard Plants (Brassica juncea L.) - Murtafaqoh, Virdha Najuba; Winarsih, Winarsih (LenteraBio : Berkala Ilmiah Biologi, 2022)
The purpose of this research were as follows: (1) determine the nutrient content of N, P, and K in liquid organic fertilizer (POC) vegetable waste leachate, (2) determine the effect of application on mustard plant (Brassica juncea L.) and (3) find the best concentration in the treatment toward the growth of mustard plant. In this research, used a one-factor Randomized Block Design (RBD), with 5 treatments and 5 repetitions as follows: L0 (0 mL/L water/polybag); L1 (5 mL/L water/polybag); L2 (10 mL/L water/polybag); L3 (15 mL/L water/polybag), L4 (20 mL/L water/polybag), then the total experiment consisted of 25 units. Growth parameters observed were plant height, the number of leaves and the fresh weight of mustard plant which were measured when the plant was 4 WAP. Analysis of the data obtained using one-way ANOVA then continued with Duncan’s test. The results showed that in POC in vegetable waste leachate contained nutrients N, P, and K were N = 0.26%; P = 0.14; and K = 0.13% which are included in the medium criteria for N and Low for P and K. The concentration of POC in vegetable waste leachate has a significant effect on all observed parameters. L4 treatment with a concentration of 20 mL/L water/polybag showed the best optimal results on the growth of mustard plant (Brassica juncea L.).